Hepatocellular carcinoma and the risk of de novo malignancies after liver transplantation – a multicenter cohort study. (26th February 2021) - Shalaby, Sarah; Taborelli, Martina; Zanetto, Alberto; Ferrarese, Alberto; D'Arcangelo, Francesca; Gambato, Martina; Senzolo, Marco; Russo, Francesco Paolo; Germani, Giacomo; Boccagni, Patrizia; Ettorre, Giuseppe Maria; Baccarani, Umberto; et al.
SUMMARY: Patients with hepatocellular carcinoma (HCC) are at high risk of second primary malignancies. As HCC has become the leading indication of liver transplant (LT), the aim of this study was to investigate whether the presence of HCC before LT could influence the onset of de novo malignancies (DNM). A cohort study was conducted on 2653 LT recipients. Hazard ratios (HR) of DNM development for patients transplanted for HCC (HCC patients) were compared with those of patients without any previous malignancy (non‐HCC patients). All models were adjusted for sex, age, calendar year at transplant, and liver disease etiology. Throughout 17 903 person‐years, 6.6% of HCC patients and 7.4% of non‐HCC patients developed DNM (202 cases). The median time from LT to first DNM diagnosis was shorter for solid tumors in HCC patients (2.7 vs 4.5 years for HCC and non‐HCC patients, respectively, P < 0.01). HCC patients were at a higher risk of bladder cancer and skin melanoma. There were no differences in cumulative DNM‐specific mortality by HCC status. This study suggests that primary HCC could be a risk factor for DNM in LT recipients, allowing for risk stratification and screening individualization.